2016
DOI: 10.1111/sode.12226
|View full text |Cite
|
Sign up to set email alerts
|

Parent emotion socialization and children's socioemotional adjustment: when is supportiveness no longer supportive?

Abstract: Parents' supportive emotion socialization behaviors promote children's socioemotional competence in early childhood, but the nature of parents' supportiveness may change over time, as children continue to develop their emotion-related abilities and enter contexts that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 67 publications
6
56
1
3
Order By: Relevance
“…However, the current study had several limitations. Although child gender and age were covariates, these variables may directly influence parents’ PA socialization, or moderate its effects (Mirabile et al, ; Root & Denham, ). Moreover, our sample consisted entirely of mothers.…”
Section: Discussionmentioning
confidence: 99%
“…However, the current study had several limitations. Although child gender and age were covariates, these variables may directly influence parents’ PA socialization, or moderate its effects (Mirabile et al, ; Root & Denham, ). Moreover, our sample consisted entirely of mothers.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, to explore the percentage of variance of parents' ERSBs explained by both parents' and children's characteristics, linear regression analyses by the stepwise method were applied. As in previous studies (e.g., [3] [26] [40]) having a moderate sample size, the use of multiple linear regression was evaluated as a good method in light of the objectives of the Study 1. Table 1 presents means and standard deviations for all measures and Table 2 presents inter-correlations between parental ERSBs, children's personality and parent's emotional competences.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies revealed that supportive parental reactions to child's emotions are related to better child's abilities in Theory of Mind (ToM) (e.g., [1] [2]), or in emotional regulation (ER) (e.g., [3] [18] [22]) and in social adjustment (e.g., [7] [11]). While parental non-supportive reactions may impede the child's socio-emotional development.…”
Section: Ersbs and Socio-emotional Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as children get older, parents may downregulate expressions of peak PA as it may become less appropriate with increased age (Lunkenheimer, Shields, & Cortina, ). There is some empirical work on NA socialization to support this conjecture (e.g., parents’ supportive responses to NA were linked to less child internalizing for younger children but more internalizing for older children; Mirabile, Oertwig, & Halberstadt, ). From the quartet papers, significant associations between children's age and youth PA regulation and maternal socialization were found with 7–12‐year‐olds (Moran et al, this issue), but the other three articles with adolescent samples did not report associations with age (Fredrick et al, this issue; Nelis et al, this issue; Raval et al, this issue).…”
Section: Moving Forwardmentioning
confidence: 99%